Contribution of Integrated Crop Livestock Systems to Climate Smart Agriculture in Argentina - Colazo, Juan Cruz; Herrera, Juan De Dios; Sager, Ricardo Luis; Guzman, Maria Laura; Zaman, Mohammad (MDPI, 2023)
Integrated crop-livestock system (ICLS) is a useful practice to enhance soil organic carbon (SOC) compared to continuous cropping systems (CC). However, robust data from different regions around the world remain to be collected. So, our objectives were to (i) compare SOC and its physical fractions in ICLS and CC, and (ii) evaluate the use of δ13C to identify the source of C of SOC in these systems in the Pampas region of Argentina. For that, we compared two farms, an ICLS and a CC having the same soil type and landscape position. The ICLS farm produces alfalfa grazed alternatively with soybean and corn, and the CC farm produces the latter two crops in a continuous sequence. Soil samples (0–5, 5–20, 20–40, and 40–60 cm) were collected and analyzed for SOC, its physical fractions, and their isotopic signature (δ13C). Soils under ICLS showed an increment of 50% of SOC stock compared to CC in the first 60 cm. This increase was related to 100–2000 µm fractions of SOC. The shift in δ13C signature is more in ICLS than in CC, suggesting that rotation with C3 legumes contributed to C sequestration and, therefore, climate-smart agriculture. The combination of on-farm research and isotopic technique can help to study deeply the effect of real farm practices on soil carbon derived from pasture.